Effect of solution-focused approach on anxiety and depression in patients with rheumatoid arthritis: A quasi-experimental study - Zhang, Chunli; Wu, Xuehua; Yuan, Ying; Xiao, Huamei; Li, Erhui; Ke, Hongyan; Yang, Mei; Zhu, Xiaodong; Zhang, Zhicheng (Frontiers in Psychology, 2022)
Introduction Anxiety and depression are common psychological problems in rheumatoid arthritis (RA) patients. However, few effective nursing intervention models have been designed specifically to improve anxiety and depression in RA patients. Solution-focused approach (SFA) is an effective intervention method for psychosocial issues. There have been no studies involving SFA yet in RA patients. This study investigated the effects of SFA-based nursing intervention on anxiety and depression in RA patients. Methods A quasi-experimental study using a convenience sampling of RA patients was conducted. The 48 RA patients were divided into the control group (n = 24) and the experimental group (n = 24). The control group received routine nursing intervention, while the experimental group received SFA-based nursing intervention. The scores on the self-rating anxiety scale (SAS), self-rating depression scale (SDS), arthritis self-efficacy scale-8 (ASES-8), and questionnaire on patient satisfaction with nursing care were collected before and after nursing interventions. Results Between-Group Comparison: Before the nursing intervention, there was no statistically significant difference in the SDS, SAS, and ASES-8 scores between the two groups (p > 0.05). However, after the nursing intervention, the SDS and SAS scores of the experimental group were statistically significantly lower than those of the control group (p < 0.05). In contrast, the ASES-8 score of the experimental group was statistically significantly higher than that of the control group (p < 0.05). In addition, patient satisfaction with nursing care of the experimental group was better than that of the control group (p > 0.05). Within-Group Comparison: There was no statistically significant difference in the SDS, SAS, and ASES-8 scores in the control group before and after routine nursing intervention (p > 0.05). However, in the experimental group, the SDS and SAS scores before SFA-based nursing intervention were statistically significantly higher than those after SFA nursing intervention (p < 0.05), and the ASES-8 score before SFA-based nursing intervention was considerably lower than that after SFA nursing intervention (p < 0.05). Discussion SFA-based nursing intervention can effectively improve anxiety, depression, and arthritis self-efficacy of RA patients. This study broadens clinical psychological nursing intervention models for RA patients. SFA may be an effective nursing model for various psychosocial problems in the current medical context.